2003
DOI: 10.1152/ajprenal.00162.2003
|View full text |Cite
|
Sign up to set email alerts
|

Partial bladder outlet obstruction alters Ca2+sensitivity of force, but not of MLC phosphorylation, in bladder smooth muscle

Abstract: Partial bladder outlet obstruction in the rabbit produces changes in bladder function similar to those seen clinically in patients with obstructive uropathies. Whole organ function is significantly altered, as are the smooth muscle cells inside the bladder wall. This study was designed to determine whether outlet obstruction alters smooth muscle function at the level of contractile filaments. Rabbit bladders were partially obstructed for 2 wk. Triton X-100 was used to provide a detergent-skinned bladder smooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Stanton et al using a skinned fibre preparation also demonstrated that there was no difference in peak force generated between the smooth muscle from control or pBOO groups [59]. In this preparation, there are also no differences in the degree of myosin light chain phosphorylation across the range of Ca 2+ concentrations.…”
Section: Myosin Light Chain Phosphorylationmentioning
confidence: 83%
“…Stanton et al using a skinned fibre preparation also demonstrated that there was no difference in peak force generated between the smooth muscle from control or pBOO groups [59]. In this preparation, there are also no differences in the degree of myosin light chain phosphorylation across the range of Ca 2+ concentrations.…”
Section: Myosin Light Chain Phosphorylationmentioning
confidence: 83%
“…However, it is unclear how these two pathways work to regulate the MLC phosphatase in agonist-stimulated bladder smooth muscle contraction. Recently, our laboratory reported an abolishment of receptor-G protein-dependent Ca 2ϩ sensitization, alterations in the MLC phosphorylation-force relationship, and loss of phorbol ester-induced contractions in a pathophysiological state of rabbit bladder smooth muscle (39,40,41). Unfortunately, the precise mechanisms underlying these important aspects of bladder smooth muscle contraction in a normal physiological state are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant with a decrease in SM-B (the high ATPase isoform) and an increase in SM-A (low ATPase isoform), there is a decrease in maximum shortening velocity and the hypertrophied detrusor smooth muscle (DSM) reveals contractile characteristics typical of tonic smooth muscle compared with the phasic contraction shown by normal DSM (46). In addition, PBOO-induced DSM hypertrophy also shows an upregulation of Rho-kinase (5) which is implicated in calcium sensitization of muscle contraction and an increase in the resting myosin light chain (MLC 20 ) phosphorylation level (8,10,44). …”
mentioning
confidence: 99%